CHANGES IN THE VELUE OF COD AND BOD IN THE THE MEDIA LIFE OF FISH SNAKESKIN GOURAMI (Trichogaster trichopterus Blkr) BY GIVEN PALM OIL WASTE WITH DIFFERENT DOSES - Suryaldi Aldo; Saberina Hasibuan; Syafriadiman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted from December 2014 to January 2015 in the Laboratory of Water Quality Management Faculty of Fisheries and Marine Sciences, University of Riau Pekanbaru. The Objective of the research was to obtain an overview of COD and BOD value changes during the study on container or media life of fish Snakeskin Gourami (Trichogaster trichopterus Blkr) by given palm oil effluent with different doses. The method used in this study is an experimental, 5 treatments and 3 replications. The treatment used in this study is P0: no palm oil waste (control), P1: 1,286 ml/L P2 : 12,86 ml/L, P3 : 25,72 ml/L, P4 : 38,58 ml/L. The results showed that each containers research by palm oil waste with different doses decreased the velue COD and BOD. The highest the COD value of 185,33 mg/L with descreased to 80,67 mg/L, and the highest the BOD value of 101,33 mg/L descreased to 41,33 mg/L, and COD value of this research is the lowest in the control treatment that is the COD value of 9.67 mg/L, and the lowest is in the BOD value of the control that is equal to 5 mg/L.Key words : Changes, COD, BOD, Palm Oil Waste, Trichogaster trichopterus